A pattern-based decision framework in the era of Industry 4.0. (27th September 2019) - Shin, Wan Seon; Seok Lee, Yong; Dahlgaard, Jens J.
Abstract : The primary purpose of this paper is to identify human decision-making patterns that can be transformed into machine decision-making in the era of Industry 4.0. We first isolated 40 key decision attributes and 6 decision patterns based on a literature review. Subsequently, we conducted a survey study of a group of 550 respondents from 11 different industrial types to find out the importance of both the attributes and the decision patterns. The six different human decision patterns (emotion, vision, principle, information, prevention, creation) were analysed for decision problems in both the daily lives and the operational stages of a business. The principle-based decision pattern is preferred for people who work in either Industry 1.0 or 2.0, while the information-based pattern is preferred for Industry 3.0. In the era of Industry 4.0, it seems that creation- and prevention-based patterns are also considered important in addition to principle- and information-based patterns. The decision patterns proposed in this study may be applied to design machines' decision-making as a way to represent human decision makers.